Purification of Curcuminoids from Natural Deep Eutectic Solvents (NADES) Matrices Using Chromatography-Based Separation Methods - Orchidea Rachmaniah; Muhammad Rifqy Muhsin; Angga Widya Putra; Muhammad Rachimoellah (Indonesian Journal of Chemistry, 2021)
Curcuminoids can be successfully extracted from Curcuma zedoaria using natural deep eutectic solvents (NADES) as extraction solvents. However, a mixture of extracted curcuminoids, NADES, and impurities from C. zedoaria was obtained as a slurry at the end of the extraction process. Therefore, further separation and purification were required to obtain the extracted compound in high purity. Herein, two purification methods based on classical column chromatography (CCC) and solid-phase extraction (SPE), were evaluated for the purification of curcuminoids from NADES matrices after extraction. Choline chloride–malic acid–water (CCMA–H2O) and choline chloride–citric acid–water (CCCA–H2O) in the molar ratio of 1:1:18 were selected as NADES matrices due to their high solubility and stabilization capability for curcuminoids. Ethanol-conditioned silica gel (60–200 µm) was applied as the bed resin for CCC, and a C18 cartridge was used for SPE. Acetonitrile/0.1% acetic acid, water/0.1% acetic acid, and iso-propanol/0.1% acetic acid were used as mobile phases for CCC. For SPE, methanol/0.05% acetic acid and water/0.05% acetic acid were applied in the conditioning step, water/0.05% acetic acid in the washing step, and methanol/acetonitrile (1:1) in the eluting step. The SPE method produced higher recovery of curcuminoids from the CCCA–H2O and CCMA–H2O matrices (75.27% and 73.40%, respectively) compared to CCC (51.9% and 61.0%, respectively). After removing the NADES constituents from the crude extract of curcuminoids, recrystallization was attempted.